MUTU ORGANOLEPTIK DAN DAYA TERIMA PANELIS TERHADAP CRACKERS KASEMBUKAN (Paederi foetida Linn.) SEBAGAI PANGAN FUNGSIONAL - Ismawati Ismawati; R. Amilia Destryana; Nailiy Huzaimah (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Study examined of the quality of orgaoleptic and panelist preferences test of Kasembukan crackers as one of the functional foods. It is known that Kasembukan has antioxidant content and among traditional society has been used as medicine in treating diarrhea and flatulence. The treatment of the research was the combination of Kasembukan’s flour with concentrations of 2.5%, 5% and 10%. Indicators of the quality organoleptic include texture, taste, flavor and after taste. Panelist preferences test used of scale of preference from numbers 1-7 (most dislike-most like). There were 100 panelists in the study. The results showed that the best treatment on organoleptic quality and panelist acceptance was the addition of 2.5% kasembukan’s flour from leaves